MODERN APPROACHES AND FACTORS, CONTRIBUTING TO THE FORMATION OF PROFESSIONAL COMPETENCE OF AN AGRICULTURAL ENGINEER IN THE SPHERE OF LIFE SAFETY (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
The article highlights modern approaches and key factors influencing the formation of professional competence of agricultural engineers in the field of life safety. In the context of rapid technological development, digitalization of agricultural production and increased requirements for safe operation of agricultural machinery, the training of specialists requires a comprehensive and multi-level approach. It includes a combination of theoretical training, practical training, digital technologies and active learning methods, aimed at the development of the competencies, required to work in the field of safety. It has been shown that the use of interactive and problem-oriented teaching methods, such as the case-stage method, the discussion method, heuristic questions and paraphrases, semantic echo, mirror and others, integrated into lectures and practical classes in discipline "Life Safety", contributes to a deeper assimilation of the theoretical material. These methods ensure not only the transfer of knowledge but also the development of analytical thinking, the ability to predict risks, make decisions in non-standard situations and work in a team, which is an important component of the professional training of agricultural engineers. There have been identified the key factors, influencing the training efficiency of specialists in this field, including: motivation of the students, based on the awareness of the importance of safety in professional activities; availability of modern educational resources; the level of qualification of the teaching staff, including the knowledge of innovative educational technologies and practical experience in the field of safety; interaction with employers and specialized organizations, facilitating the implementation of students' project activities and industrial practices in real conditions. Within the framework of the study there is assessed the efficiency of modern approaches to the development of professional competence in the field of life safety. The results showed that the introduction of active learning methods and digital tools increases the assimilation level of the material by 35-40%, increases the students’ motivation by 50%, and helps improve the practical skills to predict and prevent risks by 30-45%, compared to the traditional teaching methods. A conclusion is made about the need to create an adaptive educational system that will ensure the formation of sustainable professional competencies of agricultural engineers in the field of life safety. This system should take into account the contemporary challenges, the labour market requirements and ensure the training of specialists capable of risk analysis, making informed decisions and implementing innovative solutions in the field of agricultural engineering.